Indexed Literature as a Foundation for Inductive and Deductive Reasoning: The Triad of Research Methodology, Statistical Analysis, and Ethical Publishing in the AI Era - Balakumar, Pitchai; Thangiah, Murugan; Pandiaraj, Saravanan; Nagarkar, Shubhada; Ilangovan, P.; Srividhya, P.K.; Malliga, R.; Ramachandran, V.; Anburaj, V.; Jagadeesh, Gowraganahalli (International Journal of Pharmaceutical Investigation, 2026)
It is imperative to address the complexities of conducting and disseminating high-quality research amidst a rapidly changing scientific environment in the era of Artificial Intelligence (AI). Despite the existence of extensive literature on idea generation, literature search, protocol writing, methods, experimental design, statistical analysis, research ethics and indexed publications, there remains a significant gap in integrating these areas with the expanding impact of AI in scholarly publishing. The symposium emphasized aligning basic concepts of research, literature search and review, protocol design, and methodological consistency with suitable statistical approaches, notably in the selection between parametric and nonparametric analyses, and in upholding ethical standards in research and publication practices using AI. Essential discussions centered on the prudent use of AI tools, underscoring their potential to enhance productivity alongside the hazards of bias, authorship integrity, and transparency. Through a blend of inductive reasoning informed by real-world studies, deductive reasoning grounded in established theoretical frameworks, and abductive reasoning described as inference to the best explanation, the symposium established a comprehensive platform to foster critical thought and evidence-based decision-making. It was posited that the combination of robust research methodology, sensible statistical techniques, rigorous adherence to ethical principles, and responsible AI use could markedly increase the quality, credibility, and reproducibility of scientific outputs. The principal objective was to bridge the gap between theoretical knowledge and practical application within contemporary research practices. Additionally, the symposium aimed to deepen participants’ understanding of study design, statistical decision-making, ethical compliance, and AI-assisted publishing, ultimately fostering responsible and high-quality scientific contributions.
Keywords: Idea generation; Inductive and deductive reasoning; Research methodology; Statistical analysis; Ethical publishing; Artificial intelligence